2018
DOI: 10.1016/j.jmbbm.2018.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behavior of surgical meshes for abdominal wall repair: In vivo versus biaxial characterization

Abstract: Despite the widespread use of synthetic meshes in the surgical treatment of the hernia pathology, the election criteria of a suitable mesh for specific patient continues to be uncertain. Thus, in this work, we propose a methodology to determine in advance potential disadvantages on the use of certain meshes based on the patient-specific abdominal geometry and the mechanical features of the certain meshes. To that purpose, we have first characterized the mechanical behavior of four synthetic meshes through biax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Meshes for abdominal surgical procedures are flexible medical devices used to treat hernias, abdominal or inguinal, by adding tension-free reinforcement that results in improved tissue integration and reparation. , Meshes have also been used as prosthetic devices for the treatment of vaginal prolapse , and urinary incontinence . In the last decade, many fundamental research has been performed on tissue compatibility, bio-integration, and mechanical properties of surgical meshes. Also, their chemical surface functionalization has resulted in significant improvements, for example, prevention of unwanted tissue adhesion, cell adhesion/de-adhesion control features, and thermosensitive and shape memory properties.…”
Section: Introductionmentioning
confidence: 99%
“…Meshes for abdominal surgical procedures are flexible medical devices used to treat hernias, abdominal or inguinal, by adding tension-free reinforcement that results in improved tissue integration and reparation. , Meshes have also been used as prosthetic devices for the treatment of vaginal prolapse , and urinary incontinence . In the last decade, many fundamental research has been performed on tissue compatibility, bio-integration, and mechanical properties of surgical meshes. Also, their chemical surface functionalization has resulted in significant improvements, for example, prevention of unwanted tissue adhesion, cell adhesion/de-adhesion control features, and thermosensitive and shape memory properties.…”
Section: Introductionmentioning
confidence: 99%
“…the model of Tuset et al, 2019). Simón-Allué et al (2015) developed the idea of measurements carried out during laparoscopic repair on an animal model to identify parameters of a hyperelastic isotropic material law and their spatial distribution in the rabbit abdominal wall (Simón-Allué et al, 2017), additionally, to study the effects of implanting surgical meshes on an animal model (Simón-Allué et al, 2018). The in vivo performance of a surgical mesh implanted in abdominal wall became another research issue.…”
Section: Introductionmentioning
confidence: 99%
“…However, He et al (2020) reported that validation of the model of a repaired abdominal wall with an implant is currently missing due to a lack of sufficient data. Simón-Allué et al (2018) proposed a combined numerical in vivo and ex vivo study, but the study concerned open repair in rabbits. Podwojewski et al (2014) investigated ex vivo strains in the human abdominal wall subjected to pressure loading in the following states: healthy (intact) and incised and repaired with an intraperitoneal implant.…”
Section: Introductionmentioning
confidence: 99%